2017
DOI: 10.1016/s0140-6736(16)30313-0
|View full text |Cite
|
Sign up to set email alerts
|

Caustic ingestion

Abstract: Corrosive ingestion is a rare but potentially devastating event and, despite the availability of effective preventive public health strategies, injuries continue to occur. Most clinicians have limited personal experience and rely on guidelines; however, uncertainty persists about best clinical practice. Ingestions range from mild cases with no injury to severe cases with full thickness necrosis of the oesophagus and stomach. CT scan is superior to traditional endoscopy for stratification of patients to emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
204
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(212 citation statements)
references
References 113 publications
3
204
1
4
Order By: Relevance
“…In the study, we found most caustic injury adults were also suicide intent with acid caustic agents (detergent or insecticides) at middle to older age in Taiwan. Therefore, this kind of injury is heavy burn to family and health care system [16]. How to improve the survival rate, shorten the hospital stay and decrease long-term complications are important issues.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, we found most caustic injury adults were also suicide intent with acid caustic agents (detergent or insecticides) at middle to older age in Taiwan. Therefore, this kind of injury is heavy burn to family and health care system [16]. How to improve the survival rate, shorten the hospital stay and decrease long-term complications are important issues.…”
Section: Discussionmentioning
confidence: 99%
“…As low‐grade injury rarely causes strictures, a patient with CT grade 1 may therefore not need endoscopy, not for initial assessment nor prognostication. It seems appropriate that patients with CT grade 2 injury undergo an endoscopy early in their presentation, and this is reflected in Chirica's proposed algorithm . However, given the reluctance to perform endoscopy in caustic injury beyond 24 h, these patients would still require urgent endoscopy.…”
Section: Assessment For Strictures: Endoscopy Versus Ctmentioning
confidence: 99%
“…A CTalone algorithm would have led to the same decisions as the combined CT and endoscopy approach. Using these studies in a 2017 Lancet review, 7 Chirica proposes a radiological classification of caustic injures ( Table 2). Patients with CT grade 3 require emergency surgery; CT grade 2 should be assessed by endoscopy and managed conservatively and CT grade 1 do not require endoscopy.…”
Section: Initial Diagnosis: Endoscopy Versus Computed Tomographymentioning
confidence: 99%
“…Çocuklardaki yaralanmanın derinliğine göre tedavi ve bakım şekli değişmektedir. 21 Derin koroziv özofagus yaralanmaları olmayan çocuklar oral beslenmeyi tolere edinceye kadar hastanede izlenmelidir. 4 Derin koroziv özofagus yaralanmaları olan çocuklar ise striktür gelişimi olasılığı açısından değerlendirilmelidir.…”
Section: Erken (Akut) Dönemde Bakimunclassified